Implementasi Kebijakan Kurikulum Tingkat Satuan Pendidikan - Faria Ruhana; Yesi Yuliana (JIANA ( Jurnal Ilmu Administrasi Negara ), 2010)
Policy Implementation Education Unit Level Curriculum Research in Lubuklinggau, SouthSumatra Province is using descriptive method with qualitative approaches. The purpose of thisstudy is to determine and analyze the application of the theory of Edwards III and analyzes impor-tant findings of fact in the Education Unit Level Curriculum policy implementation in Lubuklinggau,in order to development of theory. The results showed that among the four factors examined in thepolicy implementation that communication factor and resources still need improvement consis-tently in order to Education Unit Level Curriculum program can be implemented well. Importantfindings from this study that the culture was instrumental in Education Unit Level Curriculumimplementing policies